Comparison of case-based learning and traditional method in teaching postgraduate students of medical oncology - Bi, Minghong; Zhao, Zhibiao; Yang, Jingru; Wang, Yaping (Medical teacher, 2019)
Purpose: Case-based learning (CBL) is now used as a teaching strategy to promote clinical problem-solving ability. The purpose of this study was to determine whether CBL is superior to the traditional teaching method in teaching lung cancer curriculum to oncology students. Methods: This study was a randomized controlled trial, enrolled 80 first-year oncology postgraduates from Bengbu medical college in the past 3 years. They were randomized to divide into 2 groups, had courses with the same lung cancer contents and timing. The experimental group (n = 40) utilized the CBL method while the control group (n = 40) used the traditional lecture-based teaching method. A questionnaire was used to attain the students' learning satisfaction and self-efficacy of the course, and a post-study examination was used to assess end-of-course performance. Results: Complete data were obtained from participating students (n = 40 in CBL; n = 40 in traditional teaching). The CBL group performed significantly better in questionnaire and examination compared to traditional teaching groups. Students showed high levels of satisfaction and problem-solving ability in the CBL group. Conclusion: Compared with the traditional teaching method. The case teaching method is a more effective teaching method to improve the ability of problem-solving for graduate students in medical oncology.